PERSEPSI MAHASISWA TADRIS BIOLOGI IAIN KUDUS TERHADAP PEMBELAJARAN DARING - Choiriyah, Siti Zahrotul; Fikri, Achmad Ali (JURNAL BIOEDUCATION, 2021)
The Ministry of Education and Culture (Kemendikbud) Directorate of Higher Education issued Circular No. 1 of 2020 regarding the prevention of the spread of covid 19 in the world of education, in which the Kemendikbud instructs the Ministry of Education and Culture to conduct distance learning and advises students to study from their respective homes. This study aims to determine the perception of IAIN Kudus’s Tadris Biologi Students regarding the implementation of online learning. This research uses a descriptive method with a qualitative approach. The result of this study are the perception of most student towards the use of media shows effective result, students understand the mechanism of online learning but find it difficult in online learning because of the obstacles they face, namely te difficulty of internet acces, and student are not enthusiastic in learning because they do not like online learning. So it can be concluded that judging from the 3 indicators used, namely learninf media, obstacles faced and student enthusiasm,student perception are quite good. With this research, it is hoped that there will be an increase in the enthusiasm of students so that online learning can run well and can understand the learning material as a whole.